Current Practice Performance Measurement Model: A Case Study in Indonesia - Mattoasi, Mattoasi (Journal of Education and Vocational Research, 2015)
Understanding performance measurement in the public sector organization is very important in looking into the early performance of local governments. This is because having a good performance measurement model in place serves as part of the accountability to stakeholders (e.g., society as taxpayers). Choosing the right model of performance measurement will have an impact on the performance of the government. In this research, preliminary literature study conducted found that the model of performance measurement, which was used in Indonesia in the old order as well as the new order, was an old model (traditional). The traditional model tends to be input-oriented, causingthe model to be unfit or unsuitable with the current situation. In this concept paper, which also initially analyzing the contents of documents associated with Government Performance Accountability Report (LAKIP) for several years were reviewed and reveals that after the LAKIP model was applied in Indonesia, the local government performance which now focuses on the output level helps overcoming the disadvantages of the previous models in place.